“tsɑrɑŋ?” - Telephone Conversation Openings in the Rushani Language - John Terry Dundon (Studies in Applied Linguistics & TESOL, 2019)
This paper uses conversation analysis (CA) to examine telephone conversation openings in an unwritten and understudied language, Rushani, spoken primarily in remote, mountainous areas of Tajikistan and Afghanistan. In a sample of three telephone conversations, examples are sought of the four opening sequences of telephone calls originally identified by Schegloff (1986): summons-answer; identification-recognition; greetings; and initial inquiries. At first glance, telephone conversation openings in Rushani appear to skip over the greeting stage and move directly into an extended exchange of initial inquiries. However, upon closer analysis, it is argued that a Rushani word that translates as “How are you” is in fact used by conversation participants as a greeting. The paper concludes with an argument that the study supports a “universalist” position of CA as applied to calls conducted in languages other than English (Luke & Pavlidou, 2002). Despite their apparent form as initial inquiries, greetings in telephone conversations in Rushani serve precisely the same function and resolve the same “interactional issues” as greetings in other languages (Schegloff, 1986).